2017
DOI: 10.1093/mnras/stx855
|View full text |Cite
|
Sign up to set email alerts
|

A test for skewed distributions of dark matter, and a possible detection in galaxy cluster Abell 3827

Abstract: Simulations of self-interacting dark matter (SIDM) predict that dark matter should lag behind galaxies during a collision. If the interaction is mediated by a high-mass force carrier, the distribution of dark matter can also develop asymmetric dark matter tails. To search for this asymmetry, we compute the gravitational lensing properties of a mass distribution with a free skewness parameter. We apply this to the dark matter around the four central galaxies in cluster Abell 3827. In the galaxy whose dark matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…If interpreted solely as an effect of DM self-interaction, it was argued to imply a non-vanishing σ/m of the order of 10 −4 cm 2 /g [197]. However, these results have been reinterpreted using an improved kinematical analysis, obtaining σ/m ∼ 1.5 cm 2 /g in the case of contact interactions [198,199]. The DM substructure observed in Abell 520 [200,201], coincident with the hot gas and not hosting any stars, has been interpreted as suggestive of self-interacting DM in Refs.…”
Section: Dark Matter Self-interactionsmentioning
confidence: 99%
“…If interpreted solely as an effect of DM self-interaction, it was argued to imply a non-vanishing σ/m of the order of 10 −4 cm 2 /g [197]. However, these results have been reinterpreted using an improved kinematical analysis, obtaining σ/m ∼ 1.5 cm 2 /g in the case of contact interactions [198,199]. The DM substructure observed in Abell 520 [200,201], coincident with the hot gas and not hosting any stars, has been interpreted as suggestive of self-interacting DM in Refs.…”
Section: Dark Matter Self-interactionsmentioning
confidence: 99%
“…Randall et al 2008;Kahlhoefer et al 2015;Robertson et al 2017a) as well as discussions on the size of observed offsets (e.g. Bradač et al 2008;Dawson et al 2012;Dawson 2013;Jee et al 2015;Harvey et al 2017;Peel et al 2017;Taylor et al 2017;Wittman et al 2018). There is also an extensive literature on how the self-interactions affect the merger evolution and under which conditions the picture of a drag force is appropriate (e.g.…”
Section: Equal-mass Mergermentioning
confidence: 99%
“…As well as addressing whether SIDM clusters do exhibit an enhanced diversity over their CDM counterparts (or whether one or both of the Robertson et al (2018) SIDM+baryons clusters were outliers), the presence of stars and gas in these simulations enables the generation of realistic mock data sets that can be used going forward to test existing (e.g. Gnedin & Ostriker 2001;Meneghetti et al 2001;Randall et al 2008;Harvey et al 2015Harvey et al , 2017Taylor et al 2017;Kim et al 2017) or future methods of constraining the SIDM cross-section.…”
Section: Introductionmentioning
confidence: 99%